RESPONSE OF SOME VARIETY AND BIO ORGANIC FERTILIZER ON THE GROWTH AND PRODUCTION OF WATERMELON (Citrullus vulgaris Schard) - Irna Syofia; Alridiwirsah ,; Ardian Saleh Pohan (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aims og this study was to investigate the response of several varieties and bio-organic fertilizer application on the growth and production of watermelon (Citrullus vulgaris Schard). The design used was a factorial randomized block design (RAK-F) with the two factors studied, namely: Factor watermelon varieties (V) consists of a 3-stage treatment that V1 = Varieties Sun Dragon F1, V2 = Varieties Funggawa, and V3 = Varieties Sire F1. Factors giving bio-organic fertilizer (B) consists of 4 levels ie B0 = Without treatment, B1 = 2 cc / l of water, B2 = 4 cc / l of water, and B3 = 6 cc / l of water. The parameters measured were plant height, days to flowering, number of fruits per plant, number of fruit per plot, weight of fruit per plant, fruit weight per plot.The results showed that administration of watermelon varieties can have real impact on the parameters of plant height 2MST. The best varieties are V2 = Variety funggawa. Organic bio fertilizer application significantly affected the parameters of age start flowering, number of fruits per plant, number of fruit per plot, weight of fruit per plant and fruit weight per plot. Concentration of bio-organic fertilizer is best to B3 = 6 cc / l of water. The interaction between varieties and the provision of bio-organic fertilizer giving real effect on plant height parameters 2 MST.Keywords: response, growth, bio-organic fertilizer, watermelon